DNS FILTERING: A CLEAN AND POSITIVE INTERNET ENVIRONMENT IN UIN AR-RANIRY BANDA ACEH - Rusmansyah Rusmansyah; Hendy Mizuardy; Bustami Yusuf (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2018)
The rapid IT development has brought us to the different level of an era; information openness. The information is now easily accessed through the internet. It is believed that the internet comes with many things that benefited human life. Despite its advantages, the internet also will bring problems if it is improperly used. To cope with the problems, it is important to create a safe, clean, and positive internet environment. A positive internet program, initiated by Kemkominfo Indonesia, is actively distributed to achieve this goal. We observed whether this program is feasible to be applied in a university. Our experiment object is students in Universitas Islam Ar-raniry Banda Aceh. We found that most of the students, about more than 90%, believe that a positive internet environment is important to be implemented. Moreover, a positive internet environment also will give positive impact to their personality and behavior. To realize the implementation, we have compared DNS filtering products which are able to block negative-content websites. Form our experiments, we recommend that the university apply DNS Nawala because it performs better by blocking more than 40% tested negative websites, compared to the other tested DNS products. So regarding the opinion of the students, DNS Nawala is feasible to be implemented to realize a clean, safe, and positive internet environment